STRATEGI GURU DALAM KECERDASAN VISUAL-SPASIAL PADA MATA PELAJARAN SENI BUDAYA DAN PRAKARYA DI KELAS 1 SDN MAGUWOHARJO - Yuliana Putri Prastyaningsih; Maemonah Maemonah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2023)
Visual intelligence is the aim of this research is to analyze the teacher's strategy in spatial visual intelligence of grade 1 children through art and culture subjects in drawing. The purpose of research is how the teacher's strategy is in developing children's visual-spatial intelligence when learning to draw and to find out the obstacles of elementary school students in understanding drawing in elementary schools. This study used a descriptive qualitative approach and was carried out in class I of Maguwoharjo State Elementary School with 25 student participants and information from the first grade homeroom teacher using interview and observation data collection techniques. Interviews were used to obtain data and information related to children's visual-spatial intelligence when drawing. The results showed that the visual intelligence of class IA students was still relatively low in drawing activities. Students still had difficulty and confusion when asked to draw, there were students who still imitated the results of their desk mates or other friends. Of the four indicators that have been examined at the time of the observation carried out, many students are still confused and have difficulty drawing, students have not mastered drawing and solving problems. The results of teacher and student interviews in the implementation of learning to draw, only a few students could master the indicators and were able to draw well.